2016
DOI: 10.1021/acs.jpclett.6b00622
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Control of the Exciton Wave Function in Colloidal CdSe/CdS Nanocrystals

Abstract: Using multiband k·p calculations, we show that strain-engineered piezoelectricity is a powerful tool to modulate the electron-hole spatial separation in a wide class of wurtzite CdSe/CdS nanocrystals. The inherent anisotropy of the hexagonal crystal structure leads to anisotropic strain and, consequently, to a pronounced piezoelectric field along the c axis, which can be amplified or quenched through a proper design of the core-shell structure. The use of large cores and thick shells promotes a gradual departu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 44 publications
5
58
0
Order By: Relevance
“…Large core samples however show a reduced f gap despite a much smaller band edge red shift, suggesting that a different mechanism is responsible for the electron-hole separation. The results are in line however with the calculations of Segarra et al, 42 who showed that strain at the CdSe/CdS interface can lead to a reduced electron-hole overlap, which in this case can occur in the absence of a significant reduction of the NC band gap. Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Large core samples however show a reduced f gap despite a much smaller band edge red shift, suggesting that a different mechanism is responsible for the electron-hole separation. The results are in line however with the calculations of Segarra et al, 42 who showed that strain at the CdSe/CdS interface can lead to a reduced electron-hole overlap, which in this case can occur in the absence of a significant reduction of the NC band gap. Fig.…”
Section: Resultssupporting
confidence: 90%
“…While in the first case this is the result of electron delocalization into the CdS shell, with the extent of delocalization mainly determined by the rod diameter, in the latter it is possibly enabled by strain at the core/shell interface. 42 Independent results are obtained when f gap,PL is calculated from the radiative lifetimes via Fermi's golden rule. Here, contributions to the decay traces were separated into radiative processes and nonradiative trapping, and we observed that the PL QE cannot be used to directly extract τ rad from the measured PL decay time.…”
Section: Discussionmentioning
confidence: 99%
“…Materials which has small lattice mismatch, the strain-induced localization of carriers are less efficient, as the energy levels in the CB and VB shifts insignificantly 16 . This is the case with CdSe/CdS NCs, which are structures having specific properties such as mono-dispersity, narrow emission bandwidth, and high quantum yield 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of utilizing QDs for the biological sensing is the wavelength tuneability. It was reported that the emission wavelength of a QD can be adjusted by several factors including mechanical strain and internal piezoelectric field [6] [7]. The mechanism of external strain induced bandgap change can shift the emission wavelength, but normally a relatively large strain is required to have a profound bandgap changing [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%